Understanding Sector Performance : The Case of Utilities in Latin America and the Caribbean - World Bank (World Bank, 2012)
This report provides innovative approaches to better understand infrastructure sector performance by focusing on the links between key indicators for private and public utilities, and changes in ownership, regulatory agency governance, and corporate governance, among other dimensions. By linking inputs and outputs over the last 15 years, the analysis proposes key determinants that have impacted sector performance in infrastructure sectors in Latin America and the Caribbean (LAC). It is about understanding how and to what extent the effect of such elements result in significant changes in the performance of infrastructure service provision. This report focuses on the distribution segment of basic infrastructure services. It covers electricity distribution, water distribution and sewerage, and fixed telecommunications. More specifically, the report does: i) depict sector performance with a broad set of indicators that describes the current situation as well its evolution during the last 15 years; ii) propose analytical frameworks for themes less developed in the literature such as regulatory governance and corporate governance for state-owned enterprises (SOEs); iii) benchmark the institutional designs of the regulatory agencies in the region for the water and electricity sectors; and iv) analyze the relationship between sector performance and regulation, private sector participation, and corporate governance.